ANALISIS EFEKTIVITAS DAN KENDALA PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS DIGITAL DALAM PEMBELAJARAN MATEMATIKA KELAS IV SD NEGERI 23 MARAPALAM BERBASIS DEEP LEARNING - Mutia Zakbania Zarah; Olivia Aulandari; Adrias Adrias; Nur Azmi Alwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is driven by the significance of using digital learning resources in mathematics education to help students grasp abstract notions. Nevertheless, there are challenges in its application that influence its overall effectiveness. The aim of this research is to examine both the effectiveness and the challengesassociated with incorporating digital learning resources in the Mathematics curriculum for Grade IV at SD Negeri 23 Marapalam. This investigation employs a qualitative methodology with a case study framework. The participants in this research included fourth-grade educators and students at SD Negeri 23 Marapalam. Data was gathered through methods such as observation, interviews, documentation, and analysis of literature. The analysis of data followed the Miles and Huberman model, which consists of data reduction, presentation of data, and conclusion drawing. The findings indicate that the use of digital learning resources can enhance student motivation, interest, and involvement during lessons. Digital tools facilitate the understanding of mathematical concepts for students and promote a meaningful, conscious, and enjoyable deep learning experience. However, challenges remain during implementation, including inadequate facilities and infrastructure, a lack of time for preparing the resources, and students' attention being diverted due to the visual aspects of the learning tools.